LA VIA LAPAROSCÓPICA PARA LA RESTITUCIÓN DEL TRÁNSITO INTESTINAL LUEGO DE LA OPERACIÓN DE HARTMANN. Consideraciones técnicas y resultados. - Barbarisi, M.; Sarra, C. A.; Pitaco, J. I.; Alfonso, D. A.; Gómez, E.; Minetti, A. M. (Revista Argentina de Cirugía, 2022)
Background: The laparoscopic approach in the restitution of the intestinal transit after operation type Hartmann is a reasonable option, though with high index of conversion. Objetive: Analysis of results in Hartmann’s restitution by laparoscopic and conventional approach. Design: Retrospective, comparative study. Population: Patients produced in a period (1991/2009) in successive form. Laparoscopic approach 29; conventional, 30. Method: Evaluation of the pain, recovery of the intestinal movement, surgery and labor recovery. The conversion went in relation to the curve of learning, precedent of peritonitis and time passed from the first intervention. Results: Mainsprings of first surgery: Disease diverticular, 27 and cancer, 15. There were 6 intraoperative accidents, laparoscópic, 2; conventional, 4 ( Intestinal Injury) (p=0,42 %). The complications were 3, and 5 respectively. (P = 0,67) The mortality was of 2 patients for the laparoscopic group. (P=0,49) There were 5 conversions (17.2 %). Without differences between time passed of the first surgery (p = 0,32); curve of learning (p = 0,16) and precedent of peritonitis (0,65), time of recovery (p=0,80), labor recovery (p=0,87), curved of learning (p=0,16), time passed of the first surgery (p=0,32) and presence of peritonitis (p=0,65). The pain and the recovery of the intestinal movements were minor in the laparoscopic group (p=0.0001) Conclusions: The restitution of the intestinal transit after Hartmann’s operation by laparoscopic approach is possible; though with a high index of conversion in relation to the rest of the colorectal surgery, with an acceptable complication and mortality rate, minor pain and recovery of the intestinal transit...